Internalisasi Pembelajaran Pendidikan Agama Islam Melalui Kitab Tarajumah Riayatul Himmah Karya K.H Ahmad Rifai di Kelas 5 Madrasah Ibtidaiyah Rifaiyah Limpung Batang - Yusfi Ariza Ma’arif; Nurul Mubin; Sofan Rizqi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to explore the process of internalizing Islamic Religious Education learning through the book Tarajumah Riayatul Himmah by K.H. Ahmad Rifai for 5th grade students of Madrasah Ibtidaiyah Rifaiyah Limpung Batang. The focus of this study is to identify the methods, media, and results of internalizing the values ​​taught in the book in the context of Islamic religious learning in madrasas. This type of research uses Qualitative research, with descriptive field research methods, data collection methods used include interviews, documentation, and observation. The data sources used consist of primary and secondary data that are related to the results of this study. The results of the study indicate that the use of Tarajumah Riayatul Himmah as a teaching material can strengthen students' understanding of Islamic religious values, increase learning motivation, and encourage the practice of Islamic teachings in everyday life. This learning also emphasizes the importance of applying spiritual and moral values ​​in the social context of students. It is hoped that this study can contribute to the development of Islamic Religious Education learning methods that focus on yellow books, so that it can improve the quality of education in madrasas